Can Script Training Improve Narrative and Conversation in Aphasia across Etiology? - Hubbard, H. Isabel; Nelson, Lori A.; Richardson, Jessica D. (Seminars in Speech and Language, 2020)
Script training is an effective treatment of stable (e.g., stroke-induced) and progressive aphasia of varying severities and subtypes. The theoretical underpinnings of script training are discussed and include fluency-inducing conditions, speech shadowing, principles of neuroplasticity, and automatization. Script training outcomes are reviewed, with a focus on discourse in persons with stable aphasia (PWSAs) and in persons with primary progressive aphasia (PWPPAs). PWSAs and PWPPAs are able to acquire and maintain short scripted monologues or conversational dialogues, with some evidence of generalization to untrained topics and settings. Advances in both technology and access have enriched script training protocols, so they now range from no-tech written script approaches to high-tech audiovisual support and avatars. Advances in audio and/or visual support promote large amounts of practice of less errorful whole-message language processing during a fluent language inducing condition. With enough practice, users decrease reliance on supports and independently produce scripted content. Script training can be delivered in a variety of settings (individual, group, telepractice), lends itself well to homework programs, and is in accordance with the principles of neuroplasticity for neurorehabilitation. Incorporating script training into therapy programming is advantageous throughout aphasia recovery following brain injuries such as stroke. It is also beneficial for persons with progressive disease for prophylaxis, remediation, and compensation. Recommendations for implementing script training in clinical practice and future research directions are presented.
Keywords: aphasia; discourse; primary progressive aphasia; script training; scripts